Dynamics of the Hadley cell and its implication for solar energy resources over South Africa. - Mahlobo, Dawn Duduzile (My University, 2019)
This study was inspired by the need to investigate interactions between the Hadley cell, total cloud cover as well as sunshine duration over South Africa and how the Hadley cell impacts energy generation in South Africa. To diagnose the local Hadley circulation two methods are used; first the zonally averaged mass stream function, and second the stream function vector method. The two methods are applied to the ERA-Interim reanalysis data for the period 1980–2015, to calculate both the climatology and trends of the Hadley cell. Both diagnostics advocate downwards massflux being dominant over the subtropics, particularly over South Africa, yet the strength of Hadley is seasonal. Contrasts have been found between linear trends of the two diagnostics. Zonally symmetric diagnostics indicate strengthening of the Hadley cell, particularly in the subtropics of the Southern Hemisphere in winter and weakening in summer. The zonally asymmetric results indicate maximum strengthening of the Hadley over South Africa to be in spring and weakening in summer. Furthermore, maximum decrease in cloud cover and increase in sunshine duration over South Africa is in spring, implying more opportunities for solar energy generation. The causality between the Hadley cell and cloud cover as well as sunshine duration was further explored. Granger causality between the Hadley cell and cloud cover as well as the Hadley cell and sunshine duration was analysed by means of a bivariate vector autoregressive model. Suitability of the time series was tested by means of a Dickey Fuller test and both time series failed the stationary test. To attain stationarity, the time series were first differenced. The presence of Granger causality was established between the two time series, with causal direction predominantly from the Hadley cell to cloud cover. Areas of strong causality are found over the north-western parts of South Africa. However, weak causality from cloud cover to the Hadley cell does exist, with vertical velocity being the main variable responsible for this causality, and hence indirectly affects cloud cover to Hadley cell causality. Granger causality has also been established between the Hadley cell to sunshine duration and no causality from sunshine duration to the Hadley cell was established. The behaviour of the Hadley cell, rainfall and temperatures over South Africa under the RCP 8.5 scenario and its implication to energy generation was examined. The statistical downscaled data from a regional climate model CCAM is used. The Hadley cell has been strengthening and is projected to strengthen for all seasons except DJF. Consequently, rainfall is projected to decrease during all seasons. In DJF, rainfall is projected to decrease only over the western parts, while it is expected to increase over the central and eastern regions of South Africa. Mean temperatures are projected to increase during all seasons. Changes in the Hadley cell, rainfall and temperature, have strong implications to the electricity generation in South Africa. A further advantage in understanding the Hadley cell is that it could also be used to locate areas with solar potential in South Africa.
A thesis submitted to the Faculty of Science, University of the Witwatersrand, Johannesburg, in partial fulfilment of the requirements for the degree of Doctor of Philosophy (Geography and Environmental Science)
Keywords: Clouds; Stream ecology